Relacion entre test físicos específicos y rendimiento en gimnastas de elite - Leon-Prados, J. A.; Gomez-Piriz, P. T.; Gonzalez-Badillo, J. J. (Revista Internacional de Ciencias del Deporte, 2011)
We analyzed the relationship between physical-test with the performance in Parallel Bar (BP), High Bar (BF) and Pommel Horse (CA) in ten elite gymnasts. The average power expressed on rope climbing 5m (T5) and the relative strength when performing maximum repetitions of L-support pike press to handstand (MRO) was estimated, the active (A) and passive (P) hip flexibility (2A and 2P), and his abduction from 90º hip-flexion (3A and 3P) and the competitive performance by averaging Final Score (NF) in two consecutive competitions. Significant relationships show between MRO with BP (r = 0.825; p <0.05) and BF (r = 0.678; p <0.05), between NF 2A with BP (r = -0.842) and BF (r = -0.696), 3A and NF BP (r = 0.629) and between the NF 3P and CA (r = 0.652) and BF (r = 0.815). In these gymnasts significant relationships were found between the competitive performance in CA, BP and BF and the strength and flexibility physical-test.